Hollow CuS Nanoboxes as Li‐Free Cathode for High‐Rate and Long‐Life Lithium Metal Batteries. Issue 7 (12th January 2020) - Chen, Yawei; Li, Jianming; Lei, Zhanwu; Huo, Yakun; Yang, Lanlan; Zeng, Suyuan; Ding, Honghe; Qin, Yi; Jie, Yulin; Huang, Fanyang; Li, Qi; Zhu, Junfa; et al.
Abstract: Transition metal sulfides hold promising potentials as Li‐free conversion‐type cathode materials for high energy density lithium metal batteries. However, the practical deployment of these materials is hampered by their poor rate capability and short cycling life. In this work, the authors take the advantage of hollow structure of CuS nanoboxes to accommodate the volume expansion and facilitate the ion diffusion during discharge–charge processes. As a result, the hollow CuS nanoboxes achieve excellent rate performance (≈371 mAh g −1 at 20 C) and ultra‐long cycle life (>1000 cycles). The structure and valence evolution of the CuS nanobox cathode are identified by scanning electron microscopy, transmission electron microscopy, and X‐ray photoelectron spectroscopy. Furthermore, the lithium storage mechanism is revealed by galvanostatic intermittent titration technique and operando Raman spectroscopy for the initial charge–discharge process and the following reversible processes. These results suggest that the hollow CuS nanobox material is a promising candidate as a low‐cost Li‐free cathode material for high‐rate and long‐life lithium metal batteries. Abstract : Hollow CuS nanoboxes as a type of Li‐free cathode exhibit excellent cycling stability and rate capability, which makes the CuS nanoboxes a promising electrode material for Li metal batteries application. Furthermore, the lithium storage mechanism is revealed by galvanostatic intermittent titration technique and operando Raman spectroscopy for the initial charge–discharge process and the following reversible processes.